Penyuluhan Program Pendidikan Anti Korupsi di SMP untuk Membentuk Generasi Muda yang Integritas - Adiyono Adiyono; Mardani Mardani; Ahmad Fauzan; Ali Maftuuh Mutaqiin; Aqil Dhiya Ulhaq; Hasan Mustofa Al-Baihaq; Romdani; Indra Gunawan (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Community service activities are carried out by the PKM Team of STIT Ibnu Rusyd Tanah Grogot PAI Study Program by choosing a theme that attracts the attention of many people today, including students. The number of corruption cases that occur in society encourages the PPM team to provide knowledge about the crime of corruption and its legal arrangements to prevent students from being affected by acts that lead to criminal acts of corruption in various forms, therefore the PKM team chose the theme of "Counseling Anti-Corruption Education Programs in Junior High Schools to Form an Integrity Young Generation". This article aims to describe and analyze the implementation of the anti-corruption education program carried out at SMP Muhammadiyah Tanah Grogot. Anti-corruption education aims to form a young generation that has integrity and awareness about the importance of opposing corruption in society. The methods used in this research are participatory observation, interviews with students and teachers, and document analysis related to the anti-corruption education program at SMP Muhammadiyah Tanah Grogot. The results of this study are expected to provide insights and recommendations for relevant parties in developing anti-corruption education programs in schools. The recommendations generated from this journal can serve as guidelines for related parties, including schools, teachers, and policy makers, in implementing the anti-corruption education program. Thus, it is expected that the young generation involved in the program will become agents of change who have high integrity and strong awareness to fight corruption in society.